Melody Mystery: Learning Music Theory through Escape Room Puzzles - Kenneth Y. T. Lim; Kim Mai Truong; Yuxuan Wu (MDPI AG, 2023)
This paper explores the use of escape room puzzles and instructional scaffolding in teaching novice learners about basic music theory. This study used the notion of epistemic frames in games as the basis for its experiment, combined with the use of technology-based scaffolding. We examined how effective it is to engage and motivate novice learners when they are made to mimic the role of an expert in music and solve problems using their knowledge and skills in the subject. We found positive responses from participants' attitudes toward music theory and the ability to retain knowledge of the subject, as well as evidence which proves that games can have significant effects on motivation in the learning process.